The Religious Sonnets of Dylan Thomas A Study in Imagery and Meaning. - Kleinman, H. H. (Berkeley : University of California Press, 2022)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1963.
Description based upon print version of record.
JSTOR
Keywords: Thomas, Dylan, -- 1914-1953 -- Criticism and interpretation; Thomas, Dylan, -- 1914-1953.; Religious poetry, English -- History and criticism; Sonnets, Welsh -- History and criticism; Figures of speech; Poésie religieuse anglaise -- Histoire et critique; Figures of speech; Religious poetry, English; Sonnets, Welsh; Criticism, interpretation, etc